Prophylactic Administration of Vector-Encoded Porcine Granulocyte-Colony Stimulating Factor Reduces Salmonella Shedding, Tonsil Colonization, and Microbiota Alterations of the Gastrointestinal Tract in Salmonella-Challenged Swine - Bearson, Shawn M. D.; Bearson, Bradley L.; Loving, Crystal L.; Allen, Heather K.; Lee, InSoo; Madson, Darin; Kehrli, Marcus E. (Frontiers in Veterinary Science, 2016)
Salmonella colonization of food animals is a concern for animal health and public health as a food safety risk. Various obstacles impede the effort to reduce asymptomatic Salmonella carriage in food animals, including the existence of numerous serovars and the ubiquitous nature of Salmonella. To develop an intervention strategy that is non-specific yet effective against diverse Salmonella serovars, we explored the prophylactic use of a cytokine to decrease Salmonella in swine by boosting the host’s innate immune system. Granulocyte-colony stimulating factor (G-CSF) is the major cytokine regulating the production, differentiation, function, and survival of neutrophils. Neutrophils play a critical role in the response to Salmonella; therefore, we evaluated the vectored-delivery of porcine G-CSF as a prophylactic to reduce Salmonella in pigs. Crossbred pigs, five weeks of age, were intramuscularly injected with a replication-defective human adenovirus (Ad5) engineered to express porcine G-CSF (Ad5-G-CSF, n=9). Control pigs received the same Ad5 vector lacking the gene encoding G-CSF (Ad5-empty, n=7). Four days later, all pigs (n=16) were intranasally inoculated with 1 x 10e7 CFU of Salmonella enterica serovar Typhimurium UK1. At 2 and 3 days post-challenge with Salmonella, Ad5-G-CSF treated pigs shed significantly less Salmonella (~10e3 CFU/g) in their feces than Ad5-empty treated pigs (~10e4-10e5 CFU/g; P<0.05). A significant 4-log reduction in tonsil colonization was also observed in the Ad5-G-CSF treated pigs at 7 days post-challenge (P<0.05). In the gastrointestinal tract, the Peyer’s patch region of the ileum exhibited a significant 0.5 log reduction in colonization in the Ad5-G-CSF treated pigs (P<0.05). The microbiota of all challenged pigs was assessed by sequencing and analyzing the V1-V3 region of the 16S rRNA gene from fecal DNA samples. The microbial community structure of Salmonella-challenged pigs was less disturbed post-challenge in the Ad5-G-CSF treated pigs than the Ad5-empty treated pigs. This suggests that Ad5-G-CSF administration mitigated changes in the microbial community structure caused by Salmonella challenge. Collectively, these data suggest that delivery of a targeted immunostimulant to enhance neutropoiesis may be a strategy to reduce Salmonella colonization, potentially during periods of immunological stress.